Barriers and facilitators of community-based implementation of evidence-based interventions in the UK, for children and young people's mental health promotion, prevention and treatment: rapid scoping review - Abigail Thomson; Elinor Harriss; Araminta Peters-Corbett; Keili Koppel; Cathy Creswell (BJPsych Open, 2023)
Background Community-based organisations continue to take on a greater role in supporting children and young people in the UK with their mental health. However, little evidence exists on the capacity and capability of these settings to effectively implement evidence-based interventions (EBIs).